Small RNAs in regulating temperature stress response in plants - Liu, Qing; Yan, Shijuan; Yang, Tifeng; Zhang, Shaohong; Chen, Yue‐Qin; Liu, Bin (Journal of integrative plant biology, 2017)
Due to global climate change, temperature stress has become one of the primary causes of crop losses worldwide. Much progress has been made in unraveling the complex stress response mechanisms in plants, particularly in the identification of temperature stress responsive protein‐coding genes. Recently discovered microRNAs (miRNAs) and endogenous small‐interfering RNAs (siRN As) have also been demonstrated as important players in plant temperature stress response. Using high‐throughput sequencing, many small RNAs, especially miRNAs, have been identified to be triggered by cold or heat. Subsequently, several studies have shown an important functional role for these small RNAs in cold or heat tolerance. These findings greatly broaden our understanding of endogenous small RNAs in plant stress response control. Here, we highlight new findings regarding the roles of miRNAs and siRNAs in plant temperature stress response and acclimation. We also review the current understanding of the regulatory mechanisms of small RNAs in temperature stress response, and explore the outlook for the use of these small RNAs in molecular breeding for improvement of temperature stress tolerance in plants. Here, we review the new findings regarding the roles of small RNAs and their regulatory mechanisms in plant temperature stress response. We also explore the outlook for utilization of these small RNAs in molecular breeding for improvement of temperature stress tolerance in plants.